Factors affecting sensitization following kidney allograft failure. Issue 3 (6th January 2022) - Garg, Neetika; Viney, Kelley; Burger, John; Hidalgo, Luis; Parajuli, Sandesh; Aziz, Fahad; Mohamed, Maha A.; Djamali, Arjang; Mandelbrot, Didier A.
Abstract: Introduction: Management of immunosuppression in a kidney transplant recipient with a failed allograft is complex; continuation carries infectious and metabolic risks, and discontinuation can lead to sensitization. Methods: We evaluated risk factors for sensitization in 89 kidney or simultaneous kidney‐pancreas recipients, whose kidney transplant failed after January, 2013 and who were subsequently re‐evaluated for kidney transplantation. Results: Among recipients with pre graft failure cPRA < 50%, calcineurin inhibitor (CNI) continuation (OR .11, P = .003) and steroid continuation (OR .17, P = .04) were associated with significantly lower odds of developing an absolute increase in cPRA of ≥50%. Each additional HLA mismatch was associated with OR of 2.16 ( P = .02). CNI use was associated with OR of .09 ( P = .001) for increase in cPRA to ≥80% if pre graft failure cPRA was <50%, and OR of .08 ( P = .02) for increase in cPRA to ≥98% if pre graft cPRA was <80%. Anti‐metabolites were continued more often among recipients who had a <50% increase ( P = .006); however, the association was lost on multivariate analyses. Weaning off immunosuppression and higher number of HLA mismatches are associated with greater likelihood of sensitization. Conclusion: While both CNI and steroid continuation conferred some protection against increase in cPRA, CNI continuation was the only factor protecting against becoming highly sensitized.